Thioredoxin 1 in Prostate Tissue Is Associated with Gleason Score, Erythrocyte Antioxidant Enzyme Activity, and Dietary Antioxidants. (18th August 2015) - Vance, Terrence M.; Azabdaftari, Gissou; Pop, Elena A.; Lee, Sang Gil; Su, L. Joseph; Fontham, Elizabeth T. H.; Bensen, Jeannette T.; Steck, Susan E.; Arab, Lenore; Mohler, James L.; Chen, Ming-Hui; Koo, Sung I.; et al.
Abstract : Background . Prostate cancer is the most common noncutaneous cancer and second leading cause of cancer-related mortality in men in the US. Growing evidence suggests that oxidative stress is involved in prostate cancer. Methods . In this study, thioredoxin 1 (Trx 1), an enzyme and subcellular indicator of redox status, was measured in prostate biopsy tissue from 55 men from the North Carolina-Louisiana Prostate Cancer Project. A pathologist blindly scored levels of Trx 1. The association between Trx 1 and the Gleason score, erythrocyte antioxidant enzyme activity, and dietary antioxidant intake was determined using Fisher's exact test. Results . Trx 1 levels in benign prostate tissue in men with incident prostate cancer were positively associated with the Gleason score (P = 0.01 ) and inversely associated with dietary antioxidant intake (P = 0.03 ). In prostate cancer tissue, Trx 1 levels were associated with erythrocyte glutathione peroxidase activity (P = 0.01 ). No association was found for other erythrocyte enzymes. Greater Gleason score of malignant tissue corresponds to a greater difference in Trx 1 levels between malignant and benign tissue (P = 0.04 ). Conclusion . These results suggest that the redox status of prostate tissue is associated with prostate cancer grade and both endogenous and exogenous antioxidants.